Examining the impact of four teaching development programmes for engineering teaching assistants*. Issue 3 (16th March 2019) - Fong, Carlton J.; Gilmore, Joanna; Pinder-Grover, Tershia; Hatcher, Molly
Abstract: As current graduate instructors of labs and class discussions, teaching assistants (TAs) play a critical role in Science, Technology, Engineering, and Math (STEM) undergraduate education, especially as some graduate students may choose a faculty career in the future. Because of the importance of TAs and their development as scholars and instructors, we sought to determine the most effective methods of preparing engineering TAs at two research universities. We compare the impact of a teaching orientation with one of four teaching development programmes (Pedagogy Course, Advanced Practice Teaching, Workshop Attendance with Written Reflection, or Mid-Semester Student Feedback with Written Reflection) on engineering TAs' teaching efficacy and definitions of active learning. Results indicated that the Pedagogy Course consistently increased TAs' teaching efficacy and attitudes toward teaching compared with the other programmes. We also found that stand-alone Mid-Semester Student Feedback with Written Reflection enhanced TAs' efficacy for reflection and beliefs about teaching. We discuss implications for providing teaching development for graduate students and directions for future research.